STRATEGI INTERNATIONAL CONFERENCES OF ISLAMIC SCHOLARS (ICIS) IV DALAM MENGHADAPI GERAKAN TRANSNASIONAL ISLAM DI INDONESIA - Halifa Haqqi, Ida Mujtahidah, Christy Damayanti & (Transformasi, 2017)
The issues of nir-military security are increasingly become world's attention post 9/11. Thecrime of human rights abuse, faith-based attacks and terrorism is throughout the country.Indonesia seeks to shape perception of international public with the theme of moderate Islamin deradicalization program facing Transnational Islamic Movement and Organizations inIndonesia. On the other hands, endeavouring the issues is not only undertaken by the state.This study attempts to explain the strategies of the International Conferenceof Islamic Scholars (ICIS) IV as a forum initiated to promote further moderate Islam toIndonesian people facing the transnational movements. By using the concept of nationalsecurity and religious track diplomacy, this qualitative analysis research focuses onthe strategy of ICIS as a non-state actor in Indonesia’s diplomacy. The result indicates that inICIS IV viewing the transnational movements and organizations may do harm on Indonesianreligious life. ICIS IV through its co-operations with indonesian government and local islamicNGO aiming to release tensions between the peoples. Viewed from the perspective ofideology, educations and Islamic moderate principles, the strategies seen in the forum’sactions. The wide network, welcoming forum and the deep knowledges of ulama and scholarsbecame instruments that are important on supporting the state in promoting world peace.Key words: ICIS, Transnational Movements, Diplomacy, Terrorism, National Security